Hieronymus Bosch visions and nightmares - Büttner, Nils 1967- (Reaktion Books, 2023)
"Explains Bosch's paintings against the background of contemporary Dutch culture and social reality."--Inside back cover
Keywords: Bosch, Hieronymus / -1516 / Criticism and interpretation; Painting, Dutch / 16th century / Criticism and interpretation; Criticism, interpretation, etc